2010
DOI: 10.1124/mol.110.069336
|View full text |Cite
|
Sign up to set email alerts
|

The Novel UDP Glycosyltransferase 3A2: Cloning, Catalytic Properties, and Tissue Distribution

Abstract: The human UDP glycosyltransferase (UGT) 3A family is one of three families involved in the metabolism of small lipophilic compounds. Members of these families catalyze the addition of sugar residues to chemicals, which enhances their excretion from the body. The UGT1 and UGT2 family members primarily use UDP glucuronic acid to glucuronidate numerous compounds, such as steroids, bile acids, and therapeutic drugs. We showed recently that UGT3A1, the first member of the UGT3 family to be characterized, is unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 29 publications
6
54
0
Order By: Relevance
“…It is worth noting that expression of UGT3A1 in liver and kidney as well as renal expression of UGT8 were well in the range of multiple UGT1 and UGT2 genes, supporting an important contribution of these enzymes to the conjugation of lipophilic substrates in these tissues. 7,15,16 The limited number of individuals initially sequenced from normal tissues (3 pools of at least 3 RNA samples) is a significant limitation of our study. However, data were consistent with those of an independent RNA-seq dataset of 18 individual normal liver and kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that expression of UGT3A1 in liver and kidney as well as renal expression of UGT8 were well in the range of multiple UGT1 and UGT2 genes, supporting an important contribution of these enzymes to the conjugation of lipophilic substrates in these tissues. 7,15,16 The limited number of individuals initially sequenced from normal tissues (3 pools of at least 3 RNA samples) is a significant limitation of our study. However, data were consistent with those of an independent RNA-seq dataset of 18 individual normal liver and kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type and mutant UGT3A proteins were detected with anti-UGT3A1 and anti-UGT3A2 antibodies generated previously (8,9) and a peroxidase-conjugated goat anti-rabbit secondary antibody (NeoMarkers). Immunocomplexes were visualized with the SuperSignal West Pico chemiluminescent kit (Thermo Fisher Scientific) and quantified with a GE Healthcare LAS4000 scanner.…”
Section: Methodsmentioning
confidence: 99%
“…We recently characterized the substrate specificities of the UGT3A enzymes (8,9). In striking contrast to the UGT1 and UGT2 families, we found that neither UGT3A enzyme can utilize the prototypic UGT co-substrate UDP-GlcUA.…”
mentioning
confidence: 99%
See 2 more Smart Citations